LEARNING AND TEST-TAKING STRATEGIES PERFORMED BY UNIVERSITY STUDENTS IN DOING TEST OF ENGLISH PROFICIENCY (TEP): A CASE STUDY (RETAIN, 2020)
This study aims to discover learning strategies as well as test-taking strategies used by students who have successfully passed the Test of English Proficiency (TEP). The study intends to give an example of  a strategy that the other students, especially those who have not passed TEP yet, can imitate in order to aid them in both developing their English skills as well as passing TEP. The data were collected through an in-depth interview and analyzed by using the qualitative analysis model. The result revealed that the participants utilized various learning strategies to help to improve their English abilities and various test-taking strategies to assist them in passing TEP. For further findings, related to the issues, the researcher suggested to investigating the connection between learning strategies, test-taking strategies, and students’ learning style and whether they affect students’ achievement in the context of the test of English Proficiency.